Comparison of Four Classroom-Based Strategies for Middle School Students With ADHD: A Pilot Randomized Controlled Trial. Issue 11 (September 2022) - Harrison, Judith R.; Evans, Steven W.; Zatz, Jenna; Mehta, Paulomi; Patel, Aayushi; Syed, Muzzammil; Soares, Denise A.; Swistack, Nicole; Griffith, Molly; Custer, Beth A.
Middle school students with ADHD often experience negative academic outcomes. To intervene, schools frequently provide services through special education or section 504. These services include strategies, such as breaks, prompting, and sensory proprioception to remove the impact of construct-irrelevant variance. Student plans rarely include strategies, such as selfmanagement, designed to teach students skills to increase independent functioning. The purpose of this study was to compare the effectiveness of four strategies on engagement, disruptive behavior, and time to initiate tasks. Fifteen sixth and seventh grade students were randomized daily to one of four conditions. Results indicated large statistically significant differences. Social validity data indicated that students found prompting and self-management helpful, but preferred breaks and sensory proprioception. This study builds on a growing empirical base that supports the prioritization of strategies to teach skills over strategies to remove the impact of ADHD on performance.